Two new flavonol glycosides from the leaves of Cleome viscosa L. (December 2016) - Phan, Nhat Minh; Nguyen, Tan Phat; Le, Tien Dung; Mai, Thanh Chi; Phong, Mai Thanh; Mai, Dinh Tri
Graphical abstract: Highlights: From the leaves of Cleome viscosa L., two new flavonol glycosides were isolated. Six known flavonol glycosides were also isolated from this plant. Their structures were elucidated by IR, UV, HR-ESI-MS, NMR 1D and 2D experiments. Abstract: From the leaves of Cleome viscosa L., two new flavonol glycosides, named visconoside A (1 ) and visconoside B (2 ), together with six known flavonol glycosides, vincetoxicoside A (3 ), vincetoxicoside B (4 ), kaempferitrin (5 ), kaempferide 3- O - β -d -glucopyranoside 7- O -α-l -rhamnopyranoside (6 ), kaempferol 3- O - β -d -glucopyranoside 7- O -α-l -rhamnopyranoside (7 ), and isorhamnetin 3- O - β -d -glucopyranoside (8 ) were isolated by various chromatography methods. Its chemical structure was elucidated by IR, UV, HR-ESI-MS, NMR 1D and 2D experiments and compared with literatures.